Design of local area network at the laboratory of sma 2 pgri palembang - Elda Hamidha; Jimmie (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
Currently, the laboratory uses computers and LAN networks as school practical tools. During initial observations at SMA 2 PGRI Palembang, they found a problem, namely the large number of students and the lack of learning facilities to carry out activities in the computer room resulting in some students not being able to fully study in the room. computer due to the limited time for students to learn. In developing the system, the author will use the Network Development Life Cycle (NDLC) method for designing lan network infrastructure. Network Development Life Cycle (NDLC) is a method that relies on previous development processes such as business strategy planning, application development life cycle, and data distribution analysis. And can provide an overview of the design of computer network systems that in the future can be used as a reference for building a computer network that is good and efficient and easy to implement